Vibration of cold-formed steel floors with a steel form deck and gypsum-based self-leveling underlayment. Issue 13 (October 2019) - Guan, Yu; Zhou, Xuhong; Yao, Xinmei; Shi, Yu
The vibration response and static deflection of cold-formed steel floor systems with a form deck and gypsum-based self-leveling underlayment were investigated through an experimental study and a finite element analysis. The floor system was constructed with cold-formed steel joists as supports and a cold-formed steel form deck subfloor with gypsum-based self-leveling underlayment on the surface. Dynamic tests and 1 kN static tests were carried out on three specimens, and design specifications including shear resistance construction and floor width were varied to explore their effects on the fundamental frequency, damping ratio, and center deflection of floors. Then, finite element models were developed and verified with the experimental test results, and parametric studies were conducted to consider the effect of boundary conditions on the vibration performance of the same floor systems. Based on the result, a minimum limit of fundamental frequency of 10 Hz and a maximum center deflection limit under a 1 kN point load of 1 mm were recommended for cold-formed steel floor systems with a form deck and gypsum-based self-leveling underlayment. Finally, methods to calculate the fundamental frequency and center deflection of this floor systems were proposed.